Physical and Excess Properties of Ternary Mixtures of 1-butyl-3-methylimidazolium tetrafluoroborate + monoethanolamine + water at temperature from (303.15 to 353.15)K - Malyanah, Mohd Taib; Akbar, Majid Majeed; Thanapalan, Murugesan (Elsevier, 2014)
Physical properties, namely, density and refractive index of the ternary mixture consisting of 1-butyl-3-methylimidazolium tetrafluoroborate + monoethanolamine + water have been measured at temperature range from (303.15 to 353.15) K. The measured density and refractive index data were correlated as a function of concentration and temperature. The excess properties (excess molar volume and excess refractive indices) have been deduced from the experimental physical properties.